1979
DOI: 10.1002/jhet.5570160438
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins via the wittig reaction. Synthesis of methoxsalen‐5‐14C

Abstract: A new and improved synthesis of methoxsalen (3) has been developed for the preparation of specifically carbon‐14 labelled 3. Introduction of the label by a Gattermann reaction on 6‐hydroxy‐7‐methoxycoumaran (1) followed by dehydrogenation provides an intermediate 6 which, on reaction with carbethoxymethylenetriphenylphosphorane (8) and heat inversion, provides the title compound in overall yields of up to 50%. By these procedures, 3 has been prepared 14C labelled at C‐5. Alternatively, 3 may be prepared from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…3). This known compound (50,51) was alkylated with nitrobenzylbromide͞KF͞alumina. Irradiation of 13 (Rayonet photochemical reactor, 350 nm) produces coumarin in quantitative yield.…”
Section: Resultsmentioning
confidence: 99%
“…3). This known compound (50,51) was alkylated with nitrobenzylbromide͞KF͞alumina. Irradiation of 13 (Rayonet photochemical reactor, 350 nm) produces coumarin in quantitative yield.…”
Section: Resultsmentioning
confidence: 99%
“…Coumarins can be synthesized by various reactions such as Pechmann condensation reaction [45], Knoevenagel condensation reaction [48], Perkin reaction [49], Wittig reaction [50], Claisen condensation reaction [51]. Among all these reactions Pechmann reaction are the mostly used reaction which involves the simple starting materials like phenols and β-ketoesters in the presence of acidic condensing agents to produce coumarins.…”
Section: Synthesis Methods For the Preparation Of Coumarin Scaffoldmentioning
confidence: 99%
“…A subsequent reaction of 56 with dimethyl sulfate followed by treatment with sublimed sulfur and dehydrogenation produces methoxsalen 18 (Figure 14). 191 Oda et al reported the total synthesis of bergapten (19) in a nine-step reaction series. The treatment of phloroglucinol 58 with methanol at 70°C in dioxane in a sealed tube produces monomethyl derivative 59 (89% yield).…”
Section: Synthetic Approaches For the Construction Of Benzopyronesmentioning
confidence: 99%